Breast reconstruction.: Nuestra experiencia con distintas técnicas - Olazábal, Alberto; Juri, Héctor; Acosta, Fernando; Cassinasco, Angeles (Cirugía del Uruguay, 1987)
More used procedures for breas! reconstruction are presentad. In a casuistic of mastectomized patients for mammary carcinoma, one case of mammary agenesia (Poland's syndrome) is included. There were 21 cases analyzed. Basic premisas for reconstruction are stabllshed, among them are: local tissues good conditlons. The use of skin, subcutaneous tissue and adja• cent muscle flaps are needed in case of fibrotic scar, retractad skin and thoracic parietal adherences.